TOTAL ANALYSIS OF LACTIC ACID BACTERIA OF KEMBUNG FISH (Rastrelliger neglectus) WITH THE ADDITION OF PAPAYA FRUIT SARI (Carica papaya L.) - Flowerrence Christin Lamia; Joyce Christiana Valencia Palenewen; Hanny Welly Mewengkang; Henny Adeleida Dien; Engel Victor Pandey; Feny Mentang (Sam Ratulangi University, 2023)
Fish sauce is a food product that is processed through a fermentation process made from fish and fish waste which has a distinctive taste and smell and has a long shelf life. The purpose of this study was to obtain a new formula for fish sauce and product quality. The treatment in this study was to add papaya juice with different concentrations, namely 0% as a control, 5%, 10% and 15% of the weight of the fish to be used and the salt concentration to be used was 15% of the weight of the fish. The fermentation time used was 7 days, 14 days, and 21 days. The parameters to be tested were the organoleptic test, pH test, and total test for Lactic Acid Bacteria (LAB). Based on the results of the organoleptic test which includes appearance, texture, and aroma, fish sauce samples that have a concentration of 15% and fermentation time of 21 days are the most preferred and meet SNI standards. Based on the results of the pH test, all fish sauce products with the addition of papaya extract got an average pH value of 6.9-6.1, indicating that the pH has decreased so that it meets the SNI standard. Based on the results of the LAB test, the highest total Lactic Acid Bacteria produced in A4C3 samples were samples with 15% papaya juice concentration with a total LAB 1.19x10Â³ CFU / ml.Keywords: Â Lactic Acid Bacteria (LAB), Fish Soy Sauce, Papaya Juice